Relationship of Serum Vitamin B12 and Serum Homocysteine Levels with Pseudo Exfoliation Syndrome - Butt, Waqas Rahim; Humayun, Fakhar; Naeem, Saquib; Ijaz, Umar; Khan, Umair Naeem; Khan, Taimoor Ashraf (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the relationship of serum Vitamin B12 and serum Homocysteine levels with Pseudo Exfoliation Syndrome. Study Design: Cross-sectional study. Place and Duration of Study: Department of Ophthalmology, Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jun to Nov 2022. Methodology: We included 55 individuals with unilateral Pseudo Exfoliation Syndrome without glaucoma and 50 healthy individuals as controls. All participants were subjected to the assessment of serum Homocysteine levels by high-performance liquid chromatography and Vitamin B12 levels by chemi-luminescent enzyme immunoassay. Results: Thirty-two (58.18%) individuals out of 55 with unilateral Pseudo Exfoliation Syndrome had increased serum Homocysteine levels (>5umol/L). Of these 32, 25(78.12%) individuals had moderately high serum Homocysteine levels, while 7(21.87%) had severely high serum Homocysteine levels. Twenty-six (47.27%) out of 55 individuals with Pseudo Exfoliation Syndrome had decreased serum Vitamin B12 levels, while the rest 29(52.72%) had normal-range serum Vitamin B12 levels. In comparison, 7(14%) had reduced serum Vitamin B12 levels, while the rest, 43(86%), had normal serum Vitamin B12 levels. Conclusion: Our study showed that raised Hcy levels were present in individuals with PXS without glaucoma and reduced serum Vitamin B12 levels. Assessment of Hcy level in individuals presenting with PXS may be undertaken as it is a known risk factor for vasuclopathies.